Membrane Separation as a Cleaner Processing Technology for Natural Raw Rubber Processing - Devaraj, V.; Zairossani, M. N.; Pretibaa, S. (Journal of Applied Membrane Science & Technology, 2017)
Natural rubber (NR) processing had long been a process utilizing a lot of water, discharging effluent with high organic load, creating waste and malodour. In the wake of global consciousness about environment and the scarcity of water, the NR processing, raw as well as rubber product manufacturing need to be reengineered and made environmentally and economically viable. In view of this, Malaysian Rubber Board (MRB) created a paradigm shift in raw rubber processing by investigating the use of membrane separation technology to overcome some of its pertinent problems. This paper outlines the use of membrane separation technology as an alternative method to promote cleaner processing and to extract useful biochemical as a value–added product. References were made to the current R&D projects as well as give an overview of the projects that could be undertaken in the near future so as to make NR industry to be environmentally friendly and economically viable and to achieve a zero discharge through the application of membrane separation technology.